2012
DOI: 10.1002/nau.21255
|View full text |Cite
|
Sign up to set email alerts
|

A novel animal model of underactive bladder: Analysis of lower urinary tract function in a rat lumbar canal stenosis model

Abstract: This rat model requires a relatively simple surgical procedure and has characteristics of neurogenic UAB. It seems to be useful in the pathophysiological elucidation of UAB and might have potential for assessment of pharmacotherapy of UAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
3
29
1
Order By: Relevance
“…An aliquot of urine was collected before each experiment and examined microscopically for leukocytes in order to rule out significant urinary tract infection (UTI). As shown in the previous study [7], UTI was not identified on urinalysis at CMG, and histological studies of the bladder specimens showed no obvious qualitative difference between sham and LCS rats. Also, there was no significant renal impairment on blood chemistry at the time of CMG.…”
Section: Methodssupporting
confidence: 70%
See 3 more Smart Citations
“…An aliquot of urine was collected before each experiment and examined microscopically for leukocytes in order to rule out significant urinary tract infection (UTI). As shown in the previous study [7], UTI was not identified on urinalysis at CMG, and histological studies of the bladder specimens showed no obvious qualitative difference between sham and LCS rats. Also, there was no significant renal impairment on blood chemistry at the time of CMG.…”
Section: Methodssupporting
confidence: 70%
“…This study further explored awake cystometric findings from a previous study [7]. The procedures of model preparation and the awake cystometric study are briefly described as below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the evaluated time points of this study, the effects caused by sucrose ingestion on bladder function may be associated with increased drinking volumes leading to larger bladders, without activating oxidative stress pathways, a situation observed in rats with lumbar canal stenosis or diabetes [16,17]. Accordingly, the detrusor hypertrophy detected during sucrose feeding [14], but not oxidative cell or nerve damage, strongly supports the hypothesis of altered regulation of transmitter release sources leading to underactive bladder dysfunction [12].…”
Section: Discussionsupporting
confidence: 71%